The Effect of Islamic Financing Schemes on Risk and Financing Performance in Islamic Banks in Indonesia - Ahmad Roziq; Hari Sukarno (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
The purpose of this study is to prove the effect of the financing scheme on financing risk and financing performance in Islamic banks in Indonesia. This research applies a form of quantitative research with the type of explanatory research that aims to accept or reject hypotheses. The population in this study are Islamic banks in Indonesia. The data used in the study are secondary data in the form of financial ratios sourced from Islamic bank financial reports for 2015 to 2019. Data analysis techniques use partial least squares which are used to test the inner model and outer model. The results of the study found that the sharia financing scheme that uses the buying and selling system and the profit sharing system has a significant effect on the risk of financing. However, the sharia financing scheme that uses the lease system has no significant effect on financing risk. The results also found that financing risk has a significant effect on the performance of Islamic bank financing in Indonesia. The results showed that the management of Islamic banks must be able to manage buying and selling financing and profit-sharing and profit-sharing financing schemes carefully and minimizing the risk of financing.